The effect of exercise on cytokines: implications for musculoskeletal health: a narrative review - Sophie Docherty; Rachael Harley; Joseph J. McAuley; Lindsay A. N. Crowe; Carles Pedret; Paul D. Kirwan; Stefan Siebert; Neal L. Millar (BMC, 2022)
Abstract The physiological effects of physical exercise are ubiquitously reported as beneficial to the cardiovascular and musculoskeletal systems. Exercise is widely promoted by medical professionals to aid both physical and emotional wellbeing; however, mechanisms through which this is achieved are less well understood. Despite numerous beneficial attributes, certain types of exercise can inflict significant significant physiological stress. Several studies document a key relationship between exercise and immune activation. Activation of the innate immune system occurs in response to exercise and it is proposed this is largely mediated by cytokine signalling. Cytokines are typically classified according to their inflammatory properties and evidence has shown that cytokines expressed in response to exercise are diverse and may act to propagate, modulate or mitigate inflammation in musculoskeletal health. The review summarizes the existing literature on the relationship between exercise and the immune system with emphasis on how exercise-induced cytokine expression modulates inflammation and the immune response.